A light emitting diode in a child's airway - Chan, Lucy; Yik, Yee Ian; Subramaniam, K.N.; Ramanujam, T.M. (Faculty of Medicine, University of Malaya, 2002)
A case of unusual foreign body aspiration in a child was managed recently. The mainstay in treatment is urgent extraction of the aspirated foreign body via a bronchoscope under general anaesthesia. A thoracotomy may sometimes be required when endoscopic retrieval fails, as illustrated by this case. She had an increased hospital stay of 16 days, was ventilated for 8 days and her most serious complication was septic shock from which she recovered.